Structural and Molecular Dynamics Investigation of Bacterial and Fungal Xylanases - Komari, Noer; Sanjaya, Rahmat Eko; Putra, Andifa Anugerah; Putri, Amaris Nathania Hanindia; Febriyanti, Nur Fatma (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2024)
Xylanase is a type of enzyme that hydrolyzed of β-1,4 glycosidic bonds in xylan, breaking it down into its constituent monomers. Xylanolytic enzymes are pivotal in processes such as bio-bleaching of pulp, textile manufacturing, and the recycling of waste paper. Successful bioconversion of xylan or lignocellulose relies on the collaborative action of various xylanolytic enzymes, including endo-xylanase, β-xylosidase, and other accessory enzymes. Docking simulations using Auto Dock 4.2 were conducted to analyze the interaction between ligands and xylanase, utilizing PDB 1B3V and 1FCE. Ligand interaction with xylanase was further investigated through molecular dynamics. The xylanase from Penicillium simplicissimum (PDB 1B3V) exhibited comparable affinities for α-D-xylopyranose and β-D-xylopyranose. In contrast, the xylanase from Clostridium cellulolyticum (PDB 1FCE) demonstrated a stronger affinity for β-D-glucopyranose than for 4-thiouridine. Molecular dynamic investigations indicated the stability of both structures against the tested ligands. These findings provide a foundation for potential experimental validations and the application of molecular mechanics techniques. Such approaches could unveil the detailed catalytic mechanism and bolster the industrial efficacy of the enzyme.